Kadadjiny Dwank (listening, thinking and learning with your ears): Otitis Media from an Urban Aboriginal perspective - Walley, Rosemary (Curtin University, 2020)
This thesis reports on the Kadadjiny Dwank (listening, thinking and learning with your ears) research project on otitis media (OM), or middle ear disease, conducted in partnership with local Aboriginal health organisations in two areas of Perth, Western Australia. Focused on the experiences and needs of urban Aboriginal families and their children suffering with OM, Kadadjiny Dwank is believed to be the first qualitative and urban-focused project on this issue, contributing to an identified research gap.